PENGARUH BOOK TAX DIFFERENCES TERHADAP PERTUMBUHAN LABA - Amos Rico Brolin; Abdul Rohman (Diponegoro Journal of Accounting, 2014)
This study aims to find empirical evidence about the influence of book-tax differences on the earnings growth. Population of this research manufacturing companies listed in Indonesia Stock Exchange (IDX) from 2008-2012. Sampling is done by using purposive sampling method. Sample of this study is composed of 355 companies during the five years observation. This study used multiple linear regression analysis for testing the influence of independent variables on dependent variable. The results showed that temporary differences has significant effect on the earnings growth. Permanent differences has no significant effect on the earnings growth one period ahead